Role of the Nlrp3 Inflammasome in Microbial Infection - Anand, Paras K.; Malireddi, R.K. Subbarao; Kanneganti, Thirumala-Devi (Frontiers in Microbiology, 2011)
The intracellular Nod-like receptor Nlrp3 has emerged as the most versatile innate immune receptor because of its broad specificity in mediating immune response to a wide range of microbial or danger signals. Nlrp3 mediates assembly of the inflammasome complex in the presence of microbial components leading to the activation of caspase-1 and the processing and release of the pro-inflammatory cytokines IL-1β and IL-18. In this review, we give an update on the recent literature examining the role of Nlrp3 inflammasome in response to fungal, bacterial and viral infections.